Special Economic Zones in Tajikistan: An Economic Policy Instrument for Development? - Andrei Dörre (Kulturní Studia)
Special Economic Zones (SEZs) have gained international prominence as instruments of economic policy intended to attract investment, stimulate industrial development, and reduce regional disparities. This article examines the implementation and performance of SEZs in Tajikistan—a low-income, post-Soviet economy marked by structural fragility, high labour migration, and pronounced regional inequalities. Drawing on two case studies, the Sughd and Ishkoshim Free Economic Zones (FEZ), the article demonstrates that while SEZs hold theoretical promise, their practical outcomes are highly contingent on infrastructural quality, geopolitical stability, and broader macroeconomic conditions. The Sughd FEZ has achieved modest success due to favourable location and infrastructure, whereas Ishkoshim FEZ illustrates the limits of overambitious planning in the absence of basic investment conditions. Overall, the contribution of SEZs to Tajikistan’s industrial output remains negligible, and the policy objective of mitigating regional disparities remains unmet. These findings underscore the importance of contextualised policy design and caution against overreliance on SEZs as a one-size-fits-all development tool.